The glucoregulatory action of glucagon-like peptide-1 (GLP-1). - Adamczyk, Malgorzata. (University of Ottawa (Canada), 1995)
Glucagon-like peptide-1 (GLP-1) has been shown to improve tolerance to glucose. It has been suggested that this could be mediated by an incretin effect--the enhancement of insulin secretion in response to glucose, as well as by alterations in the sensitivity of the body to insulin. In order to evaluate the effect of GLP-1 on the improvement of glucose tolerance, the systemic as well as tissue-specific (the liver, intestine and muscle) effects of this hormone have been determined. The study has been conducted on animal model (the pig). Following an overnight fast and baseline measurements, glucose was infused (set point = 150 mg/dl), alone or supplemented with GLP-1 (4 ng/kg/min) and GLP-1 (8 ng/kg/min) in 90 min steps. The levels of metabolites (glucose, lactate) and hormones (insulin, glucagon, GLP-1) were then determined in arterial blood as well as in portal, hepatic and femoral venous blood. Tissue balances were then calculated. Levels of metabolites and hormones, glucose infusion rates and tissue balances were compared using statistical analysis (general linear models procedure, SAS Institute). (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.